A Comparative Analysis of Ulama Opinions on the Existence of the Sighat Ta'liq Talaq in Indonesia - Fizal, Ahmad (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2025)
This research is descriptive-analytical in nature, aiming to describe the object of study while also conducting an in-depth analysis of it. The research method used is qualitative research, specifically library research, employing a qualitative descriptive approach that focuses on theories, concepts, and ideas. This approach seeks to reveal or describe the data or theories obtained. In classical Islamic jurisprudence (fiqh), particularly within the Shafi'i school of thought, ta'liq talaq (conditional divorce) is considered a unilateral declaration by the husband that links the occurrence of divorce to a specific condition. If the husband violates the agreement, the divorce is deemed to take effect automatically—without the wife's consent or a ruling from the religious court. However, in practice, this can lead to legal uncertainty and the potential for abuse. In contrast, under the Compilation of Islamic Law (KHI) as applied in Indonesia, ta'liq talaq is more formally and procedurally regulated. Article 45 of the KHI states that ta'liq talaq may be established as a valid marital agreement, but its declaration is not mandatory. If it is declared, it must be recorded in the marriage certificate and signed by the husband as authentic evidence. A violation of this conditional divorce agreement can only be used as a ground for divorce if submitted through a formal divorce application to the Religious Court, and the resulting divorce is not automatically considered a triple divorce (talaq tiga). According to a dictionary of fiqh terms, ta'liq talaq is defined as